(untitled) (Research, Society and Development, 2022)
Cervico-vaginal oncotic colpocytology is an important cervical cancer screening test that must be performed by women periodically, including during pregnancy. Despite not being its main objective, the exam is capable of diagnosing some species of vaginal parasites, even in asymptomatic patients. The aim of this study was to report a case of vaginal parasitosis in a pregnant woman diagnosed at the Center for the Prevention of Gynecological Diseases of the Escola Paulista de Medicina of the Federal University of São Paulo and its treatment. The present document reports the case of a primiparous pregnant woman who was referred to the tertiary service for persistent vaginal bleeding in the first gestational trimester and who, during investigation, was diagnosed with vaginitis and the rare finding of Enterobius vermicularis eggs on cervical oncotic cytology. -vaginal. The success of the treatment is not the main challenge, but the prevention of reinfection or autoinfection. For this, hygiene habits should be encouraged to all members of the household, such as: washing hands frequently, avoiding scratching the anal area, performing daily hygiene with orientation of the hands from anterior to posterior and not sharing towels and personal hygiene items.